Improvements of the conditions of keeping of boars of foreign breeding, the impact of exercise on the production of sperm - Федяєва, А. С. (Scientific Progress & Innovations, 2018)
In the article materials are given on the use of exercise and the improvement of technological conditions for keeping of boars of foreign selection. Also the impact of the exercise on the production and quality of semen under the conditions of the current economy of the state enterprise «National Plus» of the private enterprise «National» of the Dnipropetrovsk region was studied. We established that the introduction of the exercise and the improvement of the conditions of keeping of boars of foreign breeding positively influenced on the physiological state of the boars, which led to an improvement in the quality of the sperm. Also in the conditions of farming, the best genotypes of boars-producers are revealed. One of the main is the terminal boars of the Macster line (Canadian breeding), which in all respects exceeded all other boars.